Analisis Kualitas Udara serta Pemodelan AERMOD untuk Proyeksi Pola Penyebaran Emisi Genset PT. X - Cahyani, Vivi Indah; Fadhil, Muhammad Faisal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Air quality is an important aspect in maintaining environmental sustainability in industrial work areas. In facilities that rely on backup power systems such as generator sets, emission release remains a potential source of air pollution, particularly during operation. This study investigates ambient air quality, noise levels, and models the potential dispersion of genset emissions at PT. X. Ambient air, emission, and noise measurements were conducted directly in the field. The results showed that all ambient air quality and noise parameters were below the applicable regulatory limits, with differences influenced by surrounding activities, location characteristics, and genset operation schedules. Dispersion modeling using AERMOD indicated that the highest pollutant concentrations occurred near the emission source and decreased with distance, influenced by wind direction and speed. The modeling results suggest that the environmental impact of genset emissions remains low and within acceptable limits.